Transcriptome and microbiome-immune changes across preinvasive and invasive anal cancer lesions - Lacunza, Ezequiel (2024)
Anal squamous cell carcinoma (ASCC) is a rare gastrointestinal malignancy linked to high-risk human papillomavirus (HPV) infection, which develops from precursor lesions like low-grade squamous intraepithelial lesions and high-grade squamous intraepithelial lesions (HGSILs). ASCC incidence varies across populations and poses increased risk for people living with HIV. Our investigation focused on transcriptomic and metatranscriptomic changes from squamous intraepithelial lesions to ASCC. Metatranscriptomic analysis highlighted specific bacterial species (e.g., Fusobacterium nucleatum, Bacteroides fragilis) more prevalent in ASCC than precancerous lesions. These species correlated with gene-encoding enzymes (Acca, glyQ, eno, pgk, por) and oncoproteins (FadA, dnaK), presenting potential diagnostic or treatment markers. Unsupervised transcriptomic analysis identified distinct sample clusters reflecting histological diagnosis, immune infiltrate, HIV/HPV status, and pathway activities, recapitulating anal cancer progression’s natural history. Our study unveiled molecular mechanisms in anal cancer progression, aiding in stratifying HGSIL cases based on low or high risk of progression to malignancy.